2016
DOI: 10.1021/jacs.5b13524
|View full text |Cite
|
Sign up to set email alerts
|

Highly Strained Iron(II) Polypyridines: Exploiting the Quintet Manifold To Extend the Lifetime of MLCT Excited States

Abstract: Halogen substitution at the 6 and 6″ positions of terpyridine (6,6″-Cl2-2,2:6',2″-terpyridine = dctpy) is used to produce a room-temperature high-spin iron(II) complex [Fe(dctpy)2](BF4)2. Using UV-vis absorption, spectroelectrochemistry, transient absorption, and TD-DFT calculations, we present evidence that the quintet metal-to-ligand charge-transfer excited state ((5)MLCT) can be accessed via visible light absorption and that the thermalized (5,7)MLCT is long-lived at 16 ps, representing a > 100 fold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 33 publications
4
90
0
Order By: Relevance
“…This model is, however, not supported by the available experimental and other theoretical evidence and is therefore unlikely. This does not mean, however, that the 5 MLCT should always be discounted in every system, as discussed earlier with respect to Damrauer's work [72]. Experimental studies of the [190].…”
Section: Excited States and Liesstmentioning
confidence: 97%
See 1 more Smart Citation
“…This model is, however, not supported by the available experimental and other theoretical evidence and is therefore unlikely. This does not mean, however, that the 5 MLCT should always be discounted in every system, as discussed earlier with respect to Damrauer's work [72]. Experimental studies of the [190].…”
Section: Excited States and Liesstmentioning
confidence: 97%
“…An unconventional approach to reaching the long-lived MLCT states in Fe(II) complexes was taken by Damrauer and coworkers, who designed a highly-strained [Fe(dctpy) 2 ] 2+ complex, in which the two terpyridine ligands were substituted at 6 and 6'' positions by Cl atoms [72]. While the bulky substituents resulted in a significant decrease of the ligand field strength of the complex, stabilizing the quintet ground state, this structural change resulted in a more than 100fold increase in the lifetime of the excited 5,7 MLCT states compared to [Fe(bpy) 3 Overall, these specific examples illustrate that electronic structure calculations are most powerful when utilized in tandem with experimental studies to explain, corroborate, or predict the experimental results.…”
Section: Systematic and Joint Experimental/computational Studies Of Fmentioning
confidence: 99%
“…Both groups reported record MLCT lifetimes of 16-18 ps. Additionally, Shepard et al used steric bulk in ligand sets within bis-dihaloterpyrdine Fe(II) complexes to change the spin of the ground state and to achieve a 16-ps lifetime in the high-spin (quintet or septet) MLCT manifold [51]. Recently, Liu et al reported observing a record excited state lifetime of 26 ps for the 3 MLCT state of an Fe(II) complex [52].…”
Section: Impacted Areas Of Sciencementioning
confidence: 99%
“…In a different approach, using high-spin ground state halogen-substituted Fe(terpy) 2 complexes, it was shown that the 5 T 2 to 5,7 MLCT transition can lead to ≈16 ps excited-state lifetimes, which presents a more than 100-fold increase with respect to traditional Fe-polypyridine complexes [29].…”
Section: Introductionmentioning
confidence: 99%